THEORETICAL BASIS OF PERINATOLOGY THERAPY IN PREGNANT WOMEN WITH DIABETES MELLITUS - Dugalic, Stefan; Todorovic, Jovana; Macura, Maja; Gutic, Bojana; Milincic, Milos; Bozic, Dragana; Stojiljkovic, Milica; Pantic, Igor; Perovic, Milan; Gojnic, Miroslava (Sanamed, 2022)
Diabetes mellitus is a metabolic disorder that can occur before pregnancy, be detected during pregnancy, or develop during pregnancy. Therapeutic modalities available today significantly facilitate glycoregulation during pregnancy and childbirth. This review presents different insulin regimens, as well as the advantages and disadvantages of oral antidiabetic agents use with a special focus on hypoglycemia. The importance of maintaining optimal glycemic levels and educating patients in blood glucose self-measurement is explained.
Keywords: diabetes mellitus; pregnancy; insulin